Simple technique for detecting K1 antigen of Escherichia coli. - Devine, D A (1990)
The K1 antigen is a poor immunogen, its detection by serological means is difficult, and previously described methods using K1 specific bacteriophages require standardised suspensions of five different bacteriophages. A simple technique was developed which uses an unstandardised suspension of a single K1 specific bacteriophage applied with a 1 mm wire loop to bacteria streaked on to cystine lactose electrolyte deficient (CLED) medium. The technique correctly identified all 99 known K1 strains tested, including 14 strains negative with the serological method. Among 71 clinical isolates from urinary tract infections, the single bacteriophage method distinguished 30 K1 strains from 41 strains without this antigen. Suspensions of the bacteriophage were shown to remain fully active for at least two years when stored at 4 degrees C. It is concluded that this technique required so little in materials, time, or equipment that it could be routinely used in most laboratories.